Study on Axial Compressive Capacity of FRP-Confined Concrete-Filled Steel Tubes and Its Comparisons with Other Composite Structural Systems - Jun Deng; Yifeng Zheng; Yi Wang; Tonghua Liu; Hui Li (International Journal of Polymer Science)
Concrete-filled steel tubular (CFST) columns have been widely used for constructions in recent decades because of their high axial strength. In CFSTs, however, steel tubes are susceptible to degradation due to corrosion, which results in the decrease of axial strength of CFSTs. To further improve the axial strength of CFST columns, carbon fiber reinforced polymer (CFRP) sheets and basalt fiber reinforced polymer (BFRP) sheets are applied to warp the CFSTs. This paper presents an experimental study on the axial compressive capacity of CFRP-confined CFSTs and BFRP-confined CFSTs, which verified the analytical model with considering the effect of concrete self-stressing. CFSTs wrapped with FRP exhibited a higher ductile behavior. Wrapping with CFRP and BFRP improves the axial compressive capacity of CFSTs by 61.4% and 17.7%, respectively. Compared with the previous composite structural systems of concrete-filled FRP tubes (CFFTs) and double-skin tubular columns (DSTCs), FRP-confined CFSTs were convenient in reinforcing existing structures because of softness of the FRP sheets. Moreover, axial compressive capacity of CFSTs wrapped with CFRP sheets was higher than CFFTs and DSTCs, while the compressive strength of DSTCs was higher than the retrofitted CFSTs.